Pengaruh Penggunaan Media Saku Norma Terhadap Hasil Belajar Pendidikan Pancasila materi norma Kelas IV Sd Negeri Girikerto 2 - Putri, Silvi Arista Aninda; Koesmadi, Dita Primashanti; Nur'afiffah, Uci Ulfa (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this study was to determine whether the use of pocket norm media can help fourth grade students of Girikerto State Elementary School in improving their Pancasila education learning outcomes. Learning media is one of the important things in a learning process. The existence of learning media can make it easier for teachers to deliver learning materials more interactively to students. Therefore, researchers use pocket norm media to help improve their Pancasila education learning outcomes. It is hoped that with this media, students will be able to improve their learning outcomes in the field of Pancasila education better. The method used in this study is an experiment with a pre-test and posttest design. The pretest is used to see the abilities of students before being given treatment using pocket norm media. While the posttest is used to determine the abilities and learning outcomes of students after being given treatment using pocket norm media. the results obtained in the Paired Sample T-test or t-test showed that the significant value <0.05, then the hypothesis was accepted. So it can be concluded that there is a significant influence in the use of norm pocket media on improving the learning outcomes of Pancasila education on norm material for class IV at SD Negeri Girikerto 2. Although the increase is said to be in the moderate category, the existence of norm pocket media is able to provide an increase in it.